Development of Halal Tourism Through Natural Cual Woven Fabric in Sumber Harapan Village, Sambas Regency - Oggy Akmadani (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2025)
This study aims to examine the potential for developing halal tourism based on natural cual woven fabric in Sumber Harapan Village, Sambas District, and its impact on the local economy. The research method used is a qualitative approach with a descriptive method, which includes in-depth interviews, field observations, and documentation. The results of the study indicate that the process of making natural cual woven fabric, which involves traditional techniques and natural raw materials, has high cultural value and can become an attraction for educational tourism. In addition, Sumber Harapan Village has great potential to be developed into a halal tourism destination, as it has met important criteria such as worship facilities, halal food, and Muslim-friendly accommodation. The development of halal tourism based on natural cual woven fabric is expected to increase the number of tourists, create new job opportunities, and boost local income. With proper management, Sumber Harapan Village has the potential to become a sustainable tourist destination that preserves local culture and strengthens the regional economy.